Os sentidos e significados atribuídos pelo professor sobre o valor de autonomia na sua prática pedagógica - Louro, Adriana da Silva (2005)
This work intends to grasp the senses and meanings of an elementary school teacher about the autonomy value of her pedagogical practice. It is adopted the perspective of a social and historical psicology, whose phylosophic fundament is based on the dialetic historical materialism. According to that perspective, man is built on social relations, that is, on its dialectical relation with social reality. Therefore, man is not comprehended under a dichotomy of perspective that prioritize neither biological nor social aspects, but the one which is consisted by the inter relation between both. The fundamental principle of the investigation method adopted brings on the necessity of comprehension of the historical process of the object, which means the analysis of the processes that constitute the object. The research is qualitative and made with only one teacher of a public elementary school of Sao Paulo. The choice of an only subject was due to the complexity of grasping the senses and meanings constituted by an individual. The techniques used for obtaining the information were: life history, semi structured interview and analysis of a joke involving the question of autonomy. The analysis procedure was given by the organization of signification nuclei constituted on the basis of the interviewed report. The criteria used for the signification nuclei organization were: the contents that frequently showed up, that showed some significance for the interviewed, and those with some pertinence to the research objective. The authoritarianism denial appeared to be a present question in Rosana s report, being an important determinant for the understanding of her constitution of autonomy value. Authoritarianism was so present during her family and school life that she developed an abomination feeling towards it. Such feeling orients her pedagogical practice. Along her report, it is clear the concern that she would act in an authoritarian way with her pupils. Rosana makes autonomy seem natural and cannot notice it as something that is made up. On the contrary, she believes that autonomy is inherent in an individual. She makes clear in her report that she does not have a perfect understanding of the autonomy value due to its complexity. This work intends to contribute for the reflection of some aspects that can be discussed in teacher s foundation courses, such as the importance of valuing the theoretical foundation in teacher s graduation, since the lack of that theory would interfere in the pedagogical practice.